2020
DOI: 10.3389/fgene.2020.00181
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Alterations for Diagnosis, Prognosis, and Treatment of Osteoporosis: A Comprehensive Review and Computational Functional Survey

Abstract: Osteoporosis (OP) is a systemic bone disease with a series of clinical symptoms. The use of screening biomarkers in OP management is therefore of clinical significance, especially in the era of precision medicine and intelligent healthcare. MicroRNAs (miRNAs) are small, non-coding RNAs with the potential to regulate gene expression at the post-transcriptional level. Accumulating evidence indicates that miRNAs may serve as biomarkers for OP prediction and prevention. However, few studies have emphasized the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 81 publications
(82 reference statements)
0
19
0
Order By: Relevance
“…Osteoporosis is most common in post‐menopausal women where reduced circulating estrogen levels lead to an increase in both bone resorption and bone formation. However, the increase in bone resorption predominates leading to a net bone loss 87–89 …”
Section: Role Of Mir‐29 Family In Osteoporosismentioning
confidence: 99%
“…Osteoporosis is most common in post‐menopausal women where reduced circulating estrogen levels lead to an increase in both bone resorption and bone formation. However, the increase in bone resorption predominates leading to a net bone loss 87–89 …”
Section: Role Of Mir‐29 Family In Osteoporosismentioning
confidence: 99%
“…Accumulating reports have suggested that miRNAs may serve as biomarkers for OP prediction and prevention. 28 Several differentially expressed miRNAs have been identified for OP diagnosis, such as miR-103-3p, miR-30b-5p, miR-1423p, and miR-328-3p and OP, through animal experiments and analysis. 29 The lncRNA-NEF found in the study of triple-negative breast cancer could regulate miR-155 to affect the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…OPG, RANK, and RANKL are molecules of the tumor necrosis factor (TNF) and its receptor superfamily [61,62], with a pivotal role in bone metabolism that was discovered at the end of the last century [63,64]. RANKL, also known as osteoprotegerin ligand (OPGL), osteoclast differentiation factor (ODF), TNF-related activation-induced cytokine (TRANCE), or TNFSF11 (TNF ligand superfamily member 11), is a homotrimeric transmembrane protein primarily expressed by osteoblasts, osteocytes, bone marrow stromal cells, and other immune cells, such as activated T cells [61,64,65].…”
Section: Bioactivities and Mechanisms Of Action Of Essential Oilsmentioning
confidence: 99%